Guest editorial: special issue on recent advance on mobile sensor systems - Lei, Shu; Vasilakos, Athanasios V.; Lloret, Jaime; Pathan, Al-Sakib Khan (Springer New York LLC, 2011)
The continuous growing technique of sensor networks has enabled many new applications in which mobility of sensor nodes are explored, such as sea monitoring, animal migration and patrol defense. Enabling mobility in traditional static sensor networks makes a great impact on most existing research solutions and poses a large number of research challenging issues in both communication and data management aspects, which also provide lots of opportunities that researchers can leverage the mobility feature to exploring improvement for traditional solutions and methods. It is our great pleasure to bring you this special issue on “Recent Advance on Mobile Sensor Systems”, which aims at presenting innovative and significant research on the design, implementation, usage, and evaluation of mobile sensor systems, applications, and novel techniques.